Correlation of blood levels of soluble vascular cell adhesion molecule-1 with disease activity in systemic lupus erythematosus and vasculitis. - Janssen, B; Luqmani, R; Gordon, C; Hemingway, I; Bacon, P; Gearing, A; Emery, P (1994)
Levels of soluble adhesion molecules have been shown to reflect their cell surface expression in vitro, and thus may provide a useful surrogate marker of surface expression at inflammatory sites. In patients with SLE and vasculitis, serum levels of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and E-Selection were determined by ELISA during different stages of disease activity. Levels of soluble(s) VCAM-1 correlated with disease activity in patients with SLE, being significantly higher during active compared with inactive disease (P = 0.003), and normalizing with clinical remission. By contrast, in patients with vasculitis, although sVCAM-1 levels were elevated in active disease, they fell but did not normalize in inactive disease, suggesting that treatment may be suppressing the clinical manifestations rather than targeting the underlying pathogenic mechanism. Soluble ICAM-1 and E-Selectin levels did not relfect disease activity in either SLE or vasculitis.